THE EFFECT OF CHEMICAL ACTIVATION AGENTS AND ACTIVATION TEMPERATURE ON THE PORE STRUCTURE OF RICE HUSK-DERIVED ACTIVATED CARBON - Saputra, Dendi Adi; Pratoto, Adjar; Rahman, Muhammad Fadhil; Kodama, Akio (Malaysian Journal of Science, 2024)
This study investigates the optimization of production parameters for rice husk-derived activated carbon, aiming for its effective application in direct air capture (DAC) technology. Various chemical activation agents (potassium hydroxide [KOH], urea, and their combination) and activation temperatures (600°C, 700°C, and 800°C) were explored using pyrolysis. The resulting activated carbon’s morphology was analyzed via scanning electron microscopy (SEM) and ImageJ. Results demonstrate that both activation agent choice and temperature significantly influence pore diameter size and quantity. Increased temperatures led to smaller pore diameters and higher pore quantities. The combination of KOH and urea at 800°C produced the most favorable particle size (0.811 μm), suitable for applications requiring a well-defined pore structure. This combination also exhibited the most even pore distribution and highest pore density. These findings provide valuable insights for optimizing the production of rice husk-derived activated carbon, aiding in the development of sustainable and effective sorbents for CO₂ capture in DAC technology. Additionally, they offer potential for broader applications of husk-activated carbon in various industrial and environmental fields.